WORKING COOPERATIVELY, SCIENCE TEACHERS, SCIENTISTS, AND SCIENCE EDUCATORS PRODUCE A PROGRAM WHICH SIGNIFICANTLY IMPROVES ACHIEVEMENT IN SCIENCE IN THE JUNIOR HIGH SCHOOLS OF HILLSBOROUGH COUNTY, FLORIDA. - Bingham, N. Eldred (Science Education, 1963)
The article discusses a cooperative initiative launched by science teachers, scientists and science educators to improve achievement in science in the junior high schools of Hillsborough County, Florida. Special Extension Courses on the Teaching of Science were offered in the county during the school year 1959 to 1960, which were modification of usual university courses taught on the teaching of science, and were directed toward the particular problem of the improvement of the curriculum. An In-Service Institute for Junior High Science Teachers was requested and offered and a Statistical Evaluation of the Effectiveness of the In-Service Institute was made in 1961.